PHYSICAL CHARACTERIZATION OF Ni(II) DOPED TiO2 NANOCRYSTAL BY SOL-GEL PROCESS - Prasetyo Hermawan; Harno Dwi Pranowo; Indriana Kartini (Indonesian Journal of Chemistry, 2011)
Ni(II) doped titanium dioxide has been prepared by using sol-gel process. Ni(II) ion was incorporated into titanium dioxide by reacting Ni(II) chloride with titanium tetraisopropoxide (TTiP)-acetyl acetone mixture in isopropanol solvent. The effects of transition metal ion doping on the physical properties have been investigated. UV/Vis spectrophotometer, TGA-DTA, X-ray diffraction (XRD) and DR-UV/Vis were used to investigate the spectra absorption of nanosol, nanoparticle thermal transition, structure of crystal and band edge absorption, respectively. The results at addition of 5% Ni/Ti revealed that absorbance of nanosol increased from 0.811 (λmax: 342 nm) to 2.283 (λmax: 350 nm). The crystallization temperature transition from anatase to rutile decreased from 500 °C to 475 °C. The particle size increased from 18.51 nm to 20.35 nm, while the band gap energy (Eg) decreased from 2.73 eV to 2.51 eV.